2017
DOI: 10.1104/pp.16.01948
|View full text |Cite
|
Sign up to set email alerts
|

Cyst Nematode Parasitism Induces Dynamic Changes in the Root Epigenome

Abstract: A growing body of evidence indicates that epigenetic modifications can provide efficient, dynamic, and reversible cellular responses to a wide range of environmental stimuli. However, the significance of epigenetic modifications in plant-pathogen interactions remains largely unexplored. In this study, we provide a comprehensive analysis of epigenome changes during the compatible interaction between the beet cyst nematode Heterodera schachtii and Arabidopsis (Arabidopsis thaliana). Whole-genome bisulfite sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 83 publications
5
60
3
Order By: Relevance
“…The functional role of the differentially accumulated rasiRNAs in galls and syncytia (Hewezi et al., ; this article) in TE regions, which are also differentially regulated in infected tissues vs. their corresponding uninfected control tissues, is still an interesting open field of study. In line with our data, the abundance of 24‐nucleotide rasiRNAs was associated with the hypermethylation of TEs and gene promoters during the interaction of Arabidopsis with cyst nematodes (Hewezi et al., ; Piya et al., ). Further experiments are required to correlate our results in galls with methylation at these sites and to understand their implications to gall development at the early stages of infection.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The functional role of the differentially accumulated rasiRNAs in galls and syncytia (Hewezi et al., ; this article) in TE regions, which are also differentially regulated in infected tissues vs. their corresponding uninfected control tissues, is still an interesting open field of study. In line with our data, the abundance of 24‐nucleotide rasiRNAs was associated with the hypermethylation of TEs and gene promoters during the interaction of Arabidopsis with cyst nematodes (Hewezi et al., ; Piya et al., ). Further experiments are required to correlate our results in galls with methylation at these sites and to understand their implications to gall development at the early stages of infection.…”
Section: Discussionsupporting
confidence: 90%
“…sRNA libraries from Arabidopsis galls induced by M. javanica ; 3 dpi) and M. incognita (Medina et al, 2017; 7 and 14 dpi), as well as syncytia induced by the cyst nematode H. schachtii (Hewezi et al, 2008;4 and 7 dpi;Hewezi et al, 2017; 5 and 10 dpi), presented a significant enrichment in 24nucleotide sRNAs compared with control root libraries. In previous work by Cabrera et al (2016b), an analysis of sRNA length distribution suggested that the abundance of 24-nucleotide sRNAs constituted a gall hallmark, at least at early infection stages, whereas 21-nucleotide sRNAs (the length of most plant miRNAs; Axtell, 2013;Xie et al, 2015) were more abundant in uninfected roots.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A. thaliana roots infected by the cyst nematode Heterodera schachtii showed large-scale changes in DNA methylation and small RNA populations, with dynamic shifts across the infection stages. Although DNA methylation changes were probably over-estimated due to lenient calling of differentially methylated regions, epigenetic changes appeared to be associated with transcriptional changes of defense-related genes in the root (Hewezi et al, 2017).…”
Section: New Phytologistmentioning
confidence: 99%